Penyusunan soal tes bermuatan lower dan higher-order thinking skills pada guru SMP - Ega Gradini (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
Training for Junior High School’s teacher on constructing LOTS and HOTS questions aims to (1)improve teacher competence on designing lower and higher-order thinking skills assessment; and (2)provide teachers with an understanding of the formulation of successful test questions and the evaluation criteria set by the Ministry of Education and Culture. The training was given to 31 teachers of SMP IT Cendikia Takengon in stages; (1) pre-training observations; (2) tutorial and practice; (3) assistance; and (4) evaluation. The training conducted on August 14  to October 20, 2020. Based on the results of evaluation and reflection, it is found that; (1) teachers were able to write questions, both multiple-choice and essays questions, following the principles of writing questions; (2) teachers were able to understand and distinguish between cognitive levels (levels 1,2 and 3) and cognitive dimension (C1, C2, C3, C4, C5, and C6); (4) teachers generally have been able to compile HOTS questions although some teachers still have difficulty designing HOTS questions; (5) Teachers understand that HOTS questions are not difficult questions, but level 3 questions that involve reasoning; and (6) teachers understand that structured and non-structured test if properly designed have the potential to measure both lower and higher-order thinking skills.